The Mantra of Architecture Practitioners: Architectural Education is Detached From the Profession. Healing the Schism: The Need for Reformation in UK Architecture Education - Martin William Andrews (Halla Newcastle Education and Research Center, 2022)
The schism that exists between UK architecture academics and architecture practitioners is now a significant issue because the practical-knowledge gap within the profession has diminished the status of the architect as an important member of the construction team. This opinion article explores the need for tutor training in architecture education. This article draws on findings from an investigation of teacher training and staff development in Higher Education to show that the ARB, RIBA and UK Schools of Architecture could begin to develop a professional teaching and CPD framework to support architect-tutors as a way of bridging the divide between academia and practice. This article argues that if educators and practitioners can work together more harmoniously, the UK architecture profession stands a better chance of meeting a challenging and unpredictable future.